Factors Related to Depression Among Older Adults in Community, Ratchaburi Province - Malai, Chutima; Chaiyoyingyong, Rungtip; Dangdomyouth, Pennapa; Cheaplamp, Srisakul (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
The objectives of this descriptive research were to examine level of depression and to study factors related to depression among older adults. The sample was 300 older adults in Don Sai, Potharam district, Ratchaburi province, selected from the simple random sampling technique by drawing lots. The research instruments included questionnaire to collect personal factors, economic factor, family functional factors and older adult’s depression inventory. The data were analyzed by the descriptive statistics and Chi-square test. The results showed that the older adults were female (62.00%) aged between 60-69 years (43.33%). Most of them finished primary school (86.30%) and received monthly income of 500-1,000 Baht (44.3%). They lived with their spouse or their children (88.30%). According to the older adult’s depression inventory, it was found that 37.33% of them suffered from the depression. Female had more depression than male older adults. Most of them had the mild depression (70.54%) and tends to have sleep disorder in the past 2 weeks (57.99%). The factors related to the older adult’s depression included gender, status, ways of living, relationship in the family, and amount of incomes (p < .05). The findings of this study revealed that elderly women should be encouraged good relationships to prevent depression. The factors related to with depression can be used for planning and as a guideline for solving mental problems among elderly appropriately.